STRATEGI PEMASARAN CV TIMAN AGUNG KELATING KERAMBITAN TABANAN PADA MASA PANDEMI COVID 19 - Siti, N.W.; Witariadi, N. M.; Soniari, N. N.; Seminari, N. K. (Buletin Udayana Mengabdi; Vol 20 No 3 (2021): Buletin Udayana Mengabdi, 2021)
Service that aims to improve the knowledge and skills of employees of CV Timan Agung regarding marketing Strategy during the Covid 19 pandemic. The method used is counseling on marketing strategies both offline and online. Offline strategies include selling products to consumers such as Subak, Village-Owned Enterprises (Bumdes) and Regional-Owned Enterprises (Bumda). according to needs, while the online strategy is to sell various types of products using electronic / computer-based devices (Wa, Fb, masager, Youtube) so that they can be known throughout the archipelago and CV Timan Agung's revenue analysis. The result of this service is the realization of: (1) Marketing strategy through Bumdes; (2) marketing strategy through Subak (3) marketing strategy through ornamental plant shops and (3) marketing strategy through electronic media (Wa, Fb, Maseger and Youtube). The conclusions of community service during the covid 19 period are: (1) marketing of CV Timan Agung products is 100% carried out independently through offline and online, CV Timan Agung also collaborates with Bumdes Kelating in product marketing and (2) CV Timan Agung's assets such as cars increased by 50% (from 6 to 9), land in 40 acres and employees number increased by 66% (from 19 to 25 people).